The Liberian Catalogue – The Oldest (Preserved) List of the Bishops of Rome - Radulović, Nenad I. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The Liberian Catalogue represents a collection of short biographies of the bishops of Rome, starting with St. Peter, the first bishop of Rome, and ending with Pope Liberius (352–366). It is a part of an illuminated manuscript entitled The Chronograph of 354, whose author is a Roman senator named Valentinus, and it is also a valuable source of biographical information about the early bishops of Rome which has been preserved to this day. The catalogue depicts the pontificates of thirty-seven bishops of Rome, providing the years of the commencement and cessation of their pontificates, the length of their pontificates in years, months and days, and the names of the Roman emperors who were their contemporaries. In certain cases, the catalogue records significant events that came to pass within the Church during the tenure of the bishop in question or the exact date of the bishop’s death. This paper first presents the text of Liberian Catalogue based on the Chronograph of 354, edited by Theodor Mommsen and published in 1892 as part of Monumenta Germaniae Historica series, as the thirteenth part of the collection, under the title Episcopi Romani. This is then followed by a translation into Serbian, accompanied by comments and the analysis of the text.
Keywords: Liberian Catalogue; bishops of Rome; Chronograph of 354